Pengaruh Model PBL Berbantuan Video Animasi terhadap Hasil Belajar IPA - Rosiana, Siti; Rosmaiyadi, Rosmaiyadi; Setyowati , Rini (PGSD STKIP PGRI Pacitan, 2024)
The aim of this research is to determine the effect of using a problem based learning model assisted by animated videos on learning outcomes. This research was conducted at SDN 82 Singkawang. The type of research is quantitative with a quasi experimental method. This research design uses a nonequivalent comparison-group design. The research population was all fourth grade students at SDN 82 Singkawang using a non-random sampling technique. Research results: (1) There are differences in students' science learning outcomes between experimental classes 1 and 2 which were calculated using the t test with tcount>ttable, namely 6.806 > 2.00; (2) The problem based learning model assisted by animated videos has a high influence on cognitive learning outcomes in science learning of 2.154 (high criteria). (3) Improvement of the problem based learning model assisted by animated videos on students' cognitive learning outcomes is in the medium category. This can be seen from the calculation results which show a result of 0.43. So it can be concluded that the problem based learning model assisted by animated videos has a significant influence on learning outcomes in the cognitive domain.